Habit formation, work ethics, and technological progress - Jo\~ao Ricardo Faria; Miguel A. León-Ledesma (University of Kent, Department of Economics, 2002)
Work ethics affects labor supply. This idea is modeled assuming that work is habit forming. This paper introduces working habits in a neoclassical growth model and compares its outcomes with a model without habit formation. In addition, it analyzes the impact of different forms of technical progress. The findings are that i) labor supply in the habit formation case is higher than in the neoclassical case; ii) unlike in the neoclassical case, labor supply in the presence of habit formation will depend on the kind of technical progress experienced by the economy and iii) the kind of technical progress will hence affect the steady state levels of consumption, capital stock and output.
Keywords: D99; J22; O33; Z13; 330; labour supply; habit formation; work ethics; technological progress; Arbeitsethik; Arbeitsangebot; Wachstumstheorie; Neoklassik; Technischer Fortschritt; Theorie